Safety and efficacy of software-assisted MRI-TRUS fusion-guided transperineal prostate biopsy in an outpatient setting using local anaesthesia. - De Vulder, Nando; Slots, Charlotte; Geldof, Koen; Ramboer, Kristof; Dekimpe, Piet; Uvin, Pieter; Walgraeve, Marie-Sofie; Van Holsbeeck, Andries; Gieraerts, Katrien (Abdominal Radiology, 2023)
Purpose: To evaluate diagnostic accuracy, safety, and efficiency of an MRI-TRUS fusion-guided transperineal prostate biopsy method in an outpatient setting under local anaesthesia. Methods: Patients undergoing transperineal prostate biopsy were included from March 2021 to May 2022. Biopsies were performed under local anaesthesia in an outpatient setting, using specialised fusion software. Primary outcome was (clinically significant) cancer detection rate. Secondary outcomes were procedure time, patient discomfort during the procedure and complication rate. Results: We included 203 male patients (69 years +−SD 8.2) with PI-RADS score > 2. In total 223 suspicious lesions were targeted. Overall cancer detection rate and clinically significant cancer detection rate were 73.5% and 60.1%, respectively. (Clinically significant) cancer detection rates in PI-RADS 3, 4 and 5 lesions were 46.4% (23.2%), 78.5% (66.1%) and 93.5% (89.1%), respectively. Mean duration of the procedure including fusion, targeted and systematic biopsies was 22.5 min. Patients rated injection of local anaesthesia on a numeric pain rating scale on average 3.7/10 (SD 2.09) and biopsy core sampling 1.6/10 (SD 1.65). No patient presented with acute urinary retention on follow-up consultation. Two (1%) patients presented with infectious complications. Four (2%) patients experienced a vasovagal reaction. Conclusion: Transperineal targeted biopsy with MRI-TRUS fusion software has high overall and clinically significant cancer detection rates. The method is well tolerated under local anaesthesia and in an outpatient setting.